Clinical Presentation of Various Neck Masses: A Retrospective Study - Verma, Jagram; Gupta, Yamini; Saraswathi, N. (Issues and Developments in Medicine and Medical Research Vol. 3, 2022)
The department of Otorhinolaryngology has extended to include the head and neck region also.The mass in the neck is a symptom of any underlying disease in head and neck area. So hereby we use this study to have a detailed clinical knowledge and approach to various neck masses. Timely diagnosis of a neck mass is of paramount importance because delayed diagnosis leads to increased staging and worsens prognosis. Aim: To study the clinical presentation of various neck massses and the clinical differentiation of the malignant and the various non-malignant neck swellings. Materials and Methods: A retrospective study was carried out in the department of ENT, MGMMC, MYH Indore, M.P. from April 2012 to October 2013 with a total of 190 patients with neck swelling. A detailed clinical, radiological and pathological assessment of the various neck swelling had been done. Results: Out of 190 patients, 145 were non malignant and 45 were malignant and the incidence of the malignant neck swelling increased with age. Pain and fever were associated with non malignant swellings with 32.1% and 90.4% respectively. Conclusion: The methodological clinical assessment of the various neck masses led to proper diagnosis and management of the patients thus preventing any delay and complications.